Jurassic fossil juvenile reveals prolonged life history in early mammals - Panciroli, E; Benson, RBJ; Fernandez, V; Fraser, NC; Humpage, M; Luo, Z-X; Newham, E; Walsh, S (Nature Research, 2024)
Living mammal groups exhibit rapid juvenile growth with a cessation of growth in adulthood1. Understanding the emergence of this pattern in the earliest mammaliaforms (mammals and their closest extinct relatives) is hindered by a paucity of fossils representing juvenile individuals. We report exceptionally complete juvenile and adult specimens of the Middle Jurassic docodontan Krusatodon, providing anatomical data and unprecedented insights into the life history of early-diverging mammaliaforms. We used synchrotron X-ray micro CT imaging of cementum growth increments within the teeth2,3 to provide the first evidence of pace of life in a Mesozoic mammaliaform. The adult was ~7 years and the juvenile 7 to 24 months of age at death, and in the process of replacing its deciduous dentition with its final, adult generation. When analysed against a dataset of life history parameters for extant mammals4, the relative sequence of adult tooth eruption was already established in Krusatodon, and within the range observed in extant mammals, but this development was prolonged; taking place during a longer period as part of a significantly longer maximum lifespan than extant mammals of comparable adult body mass (≤156 grams). Our findings suggest early-diverging mammaliaforms did not experience the same life histories as extant small-bodied mammals, and the fundamental shift to faster growth over a shorter lifespan may not have taken place in mammaliaforms until during or after the Middle Jurassic.